The Demands of Simple and Complex Arithmetic Word Problems on Language and Cognitive Resources - Hickendorff, Marian (Frontiers in Psychology, 2021)
Solving arithmetic word problems requires constructing a situation model based on the problem text and translating that into a mathematical model. As such, word-problem solving makes demands on students’ language comprehension and their domain-general cognitive resources. These demands may decrease when students get more experienced and use strategies that so not require fully understanding the situation presented in the problem. The current study aims to address this hypothesis. Students (N = 444) from third to sixth grade solved a paper-and-pencil task with 48 mathematics problems, comprising symbolic arithmetic problems and standard word problems, as well as more complex word problems that involve two arithmetic steps or include irrelevant numerical information. Their performance was analyzed with multilevel logistic regression analyses. Results showed that within each grade performance on the different problem types did not differ, suggesting that already in third grade students seem helped nor hindered by presenting arithmetic problems in a story, even if that story contains irrelevant numerical information. Non-verbal reasoning was more important in standard word problems than in arithmetic problems in symbolic format in one-step arithmetic, and reading comprehension was more important in solving two-step arithmetic word problems than in one-step arithmetic word problems.